Enablers of Physician Prescription of a Long-Term Asthma Controller in Patients with Persistent Asthma - Francine M. Ducharme; Alexandrine J. Lamontagne; Lucie Blais; Roland Grad; Kim L. Lavoie; Simon L. Bacon; Martha L. McKinney; Eve Desplats; Pierre Ernst (Canadian Respiratory Journal)
Objective. We aimed to identify key enablers of physician prescription of a long-term controller in patients with persistent asthma. Methods. We conducted a mailed survey of randomly selected Quebec physicians. We sent a 102-item questionnaire, seeking reported management regarding one of 4 clinical vignettes of a poorly controlled adult or child and endorsement of enablers to prescribe long-term controllers. Results. With a 56% participation rate, 421 physicians participated. Most (86%) would prescribe a long-term controller (predominantly inhaled corticosteroids, ICS) to the patient in their clinical vignette. Determinants of intention were the recognition of persistent symptoms (OR 2.67), goal of achieving long-term control (OR 5.31), and high comfort level in initiating long-term ICS (OR 2.33). Decision tools, pharmacy reports, reminders, and specific training were strongly endorsed by ≥60% physicians to support optimal management. Physicians strongly endorsed asthma education, lung function testing, specialist opinion, accessible asthma clinic, and paramedical healthcare professionals to guide patients, as enablers to improve patient adherence to and physicians’ comfort with long-term ICS. Interpretation. Tools and training to improve physician knowledge, skills, and perception towards long-term ICS and resources that increase patient adherence and physician comfort to facilitate long-term ICS prescription should be considered as targets for implementation.